2012
DOI: 10.1002/ece3.319
|View full text |Cite
|
Sign up to set email alerts
|

Weak patriline effects are present in the cuticular hydrocarbon profiles of isolated Formica exsecta ants but they disappear in the colony environment

Abstract: Chemical recognition cues are used to discriminate among species, con-specifics, and potentially between patrilines in social insect colonies. There is an ongoing debate about the possible persistence of patriline cues despite evidence for the mixing of colony odors via a “gestalt” mechanism in social insects, because patriline recognition could lead to nepotism. We analyzed the variation in recognition cues (cuticular hydrocarbons) with different mating frequencies or queen numbers in 688 Formica exsecta ants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…On the one hand, at the population level genetically similar colonies are also chemically similar (Dronnet et al 2006;Van Wilgenburg et al 2010). Therefore, a genetic basis for the cues exists in a broad sense, which is also supported by studies of cuticular profile heritability (Thomas and Simmons 2008), the underlying genotype in nonsocial insects (Dallerac et al 2000;Takahashi et al 2001), and the observed patriline differences among socially isolated callow workers in Formica ants (Martin et al 2012a). On the other hand, despite relatively high genetic diversity within colonies, chemical cues can be remarkably uniform across genetically diverse nestmates Helanterä et al 2011, but see Nehring et al 2011Helanterä et al 2013, for exceptions).…”
mentioning
confidence: 83%
“…On the one hand, at the population level genetically similar colonies are also chemically similar (Dronnet et al 2006;Van Wilgenburg et al 2010). Therefore, a genetic basis for the cues exists in a broad sense, which is also supported by studies of cuticular profile heritability (Thomas and Simmons 2008), the underlying genotype in nonsocial insects (Dallerac et al 2000;Takahashi et al 2001), and the observed patriline differences among socially isolated callow workers in Formica ants (Martin et al 2012a). On the other hand, despite relatively high genetic diversity within colonies, chemical cues can be remarkably uniform across genetically diverse nestmates Helanterä et al 2011, but see Nehring et al 2011Helanterä et al 2013, for exceptions).…”
mentioning
confidence: 83%
“…[16], [20]), chemical recognition (e.g. [21][24]), social parasitism (exploitation of colony resources, [25]) and their role in forest ecosystems (e.g. [26][29]).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting complication of the genetic architecture of social insect cuticular hydrocarbon profiles (Linksvayer 2006(Linksvayer , 2015 is that the social environment experienced by each individual within a social insect colony strongly influences its hydrocarbon profile, since hydrocarbons are mixed throughout the colony via trophallaxis and allogrooming between colony members (Bonavita-Cougourdan et al 1997;van Zweden et al 2009Martin et al 2012;Khidr et al 2013;Gevar et al 2017). As a result, the genetic architecture of the hydrocarbon profile, like other socially-influenced traits, depends on the collective genetic makeup of colonies (Linksvayer 2006(Linksvayer , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the central role of cuticular hydrocarbons in insect societies, we still know very little about fundamental genetic and evolutionary features shaping social insect hydrocarbon profiles, including the relative contribution of genetic and environmental factors to phenotypic variation in hydrocarbon profiles within and between colonies (Menzel et al 2017), and how natural selection acts on this variation. Numerous studies have demonstrated that the social insect hydrocarbon profile is influenced by genotype by tracking familial lines (van Zweden et al 2009;Nehring et al 2011;Martin et al 2012, Martin et al 2013, using cross-fostering designs , or demonstrating an association between hydrocarbon diversity and within-colony genetic variation (Dronnet et al 2006;Menzel et al 2016). However, very few studies have examined the underlying genetic architecture of social insect hydrocarbons within a formal quantitative genetic framework (Boomsma et al 2003).…”
Section: Introductionmentioning
confidence: 99%